PEMBENIHAN IKAN MASKOKI (Carrasius auratus) DENGAN MENGGUNAKAN BERBAGAI SUBSTRAT Seedbed goldfish (Carrasius auratus) By Using Various Substrates - Tommy Patria Marbun; Darma Bakti; Nurmatias Nurmatias (AQUACOASTMARINE, 2015)
Goldfish spawning is done naturally, so the success of the nurseries are still low. The success of spawning is influenced by several factors, including the handling of aircraft, particularly in stimulating technological parent spawning, egg incubation and larval treatment. How that can be done to stimulate the provision of parent fish are egg laying substrate. This study aims to determine the type of engaging subsrat eggs that give the best effect on the success of spawning goldfish (Carassius auratus). This research used experimental and observational methods, research design used was a completely randomized design (CRD). Tacks substrate type eggs are used as treatment, water hyacinth (Eicchornia crassipies), rafia rope and sugar falm fiber. Each treatment was repeated three times, so there are 9 units of the experiment. The parameters measured were the number of eggs, hatchability and larval survival goldfish (Carassius auratus). The results showed that the number of fertilized eggs on each substrate goldfish obtained F count>F table then H0 is rejected, it means that there are differences in the number of eggs on the substrate for all three treatments were used. Degree of hatching eggs goldfish sugar falm fiberbest is 63.70%, 61.20% and hyacinth rafia rope 45.79%. Water quality in this study have average values: pH 7 and temperature of 28 0C.Keywords: Carassius auratus, substrates, hatchability and survival